2021
DOI: 10.1108/jme-08-2021-0161
|View full text |Cite
|
Sign up to set email alerts
|

Legacies of the COVID-19 pandemic for language education: focusing on institutes managers’ lived experiences

Abstract: Purpose This paper aims to compare the use of technology in language institutes before and amid the COVID-19 pandemic. Then, the authors illustrate the legacies of the COVID-19 pandemic for language institutes from the managers’ perspective. Design/methodology/approach In the current study, the authors went through a systematic process of collecting qualitative data, discovering sub-categories, forming categories out of them and explaining the topic under investigation using selected categories. Findings T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The government and the tertiary educational institute need to join hands and examine the optimal learning times for the undergraduates. On an institutional scale, the university can allow students to choose their study time according to their own needs (Turchi et al, 2020;Tafazoli and Atefi Boroujeni, 2021) or introduce longer intervals between synchronous sessions where students can conduct healthy practices like a breathing exercise (Mheidly et al, 2020).…”
Section: Factors Influencing English As a Foreign Language Learners' ...mentioning
confidence: 99%
“…The government and the tertiary educational institute need to join hands and examine the optimal learning times for the undergraduates. On an institutional scale, the university can allow students to choose their study time according to their own needs (Turchi et al, 2020;Tafazoli and Atefi Boroujeni, 2021) or introduce longer intervals between synchronous sessions where students can conduct healthy practices like a breathing exercise (Mheidly et al, 2020).…”
Section: Factors Influencing English As a Foreign Language Learners' ...mentioning
confidence: 99%
“…The global experiences showed that, apart from its opportunities, the transition from traditional and physical education to high-quality technology-based and online education is challenging. Therefore, the government, institutions, teachers, students, and parents, in close collaboration, should solve the challenges, including the acceptance and readiness of governments and institutions to move to online education (Bozkurt & Sharma, 2020 ), planning and modifying the policies regarding the accreditation of online education (Tafazoli & Atefi Boroujeni, 2021 ), technology-related psychological issues that affect teachers and students performance (Geng et al, 2019 ; Green et al, 2020 ), financial-related issues in equipping students and teachers with required resources (Aguilera-Hermida, 2020 ; Gillis & Krull, 2020 ), and teachers’ readiness and knowledge of effective technology-based teaching (Sepulveda-Escobar & Morrison, 2020 ; Tafazoli, 2021b ).…”
Section: Introductionmentioning
confidence: 99%